Spatial coarse graining of phase space. - Corentin Robert (20902823) (2025)
Black lines represent the different boundaries between each coarse-grained state and are given by Eqs (11) and (12). In this case, . Trajectories that are in the red, blue or grey domains corresponds to A, B or C cells respectively.